Regional Language Learning Strategies in Improving Student Language Skills at Madrasah Ibtidaiyah Negeri 1 East Kutai - Anjani Putri Belawati Pandiangan; Nurfatiya Nurfatiya; Nor Sukma Yulianti; Hanifah Zahirah; Ahmad Syahroni (Madrasah Al-Wathoniyah : Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2025)
This research aims to find out what language learning strategies are in improving the language skills of elementary school students. This research data uses the method. This research uses a qualitative approach with Kutai language teacher subjects and students in class 4 MIN 1 East Kutai. Data were collected through observations, interviews, and documentation to determine learning strategies and their impact on students' language skills. Data analysis is carried out through the stages of data collection, reduction and presentation. The object of this research was carried out at MIN 1 Sangatta Utara, the research results showed that the regional language learning strategy at MIN 1 Sangatta Utara was proven to improve students' language skills through an integrated and contextual approach. Language is taught as a communication tool to convey ideas, feelings, and information. Learning is active and varied, project, activity, and technology-based, and involves teachers, students, and parents. Four language skills—listening, speaking, reading and writing— are trained in an integrated manner. Kutai language is used in learning to increase students' self-confidence in speaking. Students are also invited to discuss, debate, write, and simulate. This helps with complete mastery of the language. Some students are more comfortable writing than speaking, so a diverse approach is needed so that all aspects of skills develop. This strategy is in line with theories that emphasize the importance of skills integration, active student participation, and a supportive learning environment.